2022
DOI: 10.3389/fvets.2022.936251
|View full text |Cite
|
Sign up to set email alerts
|

Review detection of Newcastle disease virus

Abstract: Newcastle disease (ND) is an acute and highly contagious disease caused by the Newcastle disease virus (NDV) infecting poultry, which has caused great harm to the poultry industry around the world. Rapid diagnosis of NDV is important to early treatment and early institution of control measures. In this review, we comprehensively summarize the most recent research into NDV, including historical overview, molecular structure, and infection mechanism. We then focus on detection strategies for NDV, including virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Previous reports have shown that NDV can be disseminated in the blood, so that virus can be detected in all tissues and organs after infection; however, the viral loads in tissues and organs have discrepancies between NDV genotypes ( Jia et al, 2022 ; Mao et al, 2022 ). We observed high viral loads in different tissues showed high levels in the thymus, bursa of Fabricius, intestine, liver, and spleen, with lower viral loads in the kidney, muscle, brain, and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that NDV can be disseminated in the blood, so that virus can be detected in all tissues and organs after infection; however, the viral loads in tissues and organs have discrepancies between NDV genotypes ( Jia et al, 2022 ; Mao et al, 2022 ). We observed high viral loads in different tissues showed high levels in the thymus, bursa of Fabricius, intestine, liver, and spleen, with lower viral loads in the kidney, muscle, brain, and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In result, page 11, wavenumber should be separated. it was not uniformly written in many pages, (check page 12,13). The low yield of the extract should be compared to early researchers.…”
Section: Open Peer Reviewmentioning
confidence: 99%
“…11 The severity of the infection is determined by the virulence of the infecting virus and the host susceptibility. 11,12 The occurrence of cases is reportable; they may result in trade restrictions. NDV is also known as avian paramyxovirus serotype 1 (PMV-1).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the serum antibody levels in vaccinated chickens, especially neutralizing antibody levels, are important indicators for evaluating NDV vaccination [ 13 , 14 , 15 ]. The Hemagglutination inhibition (HI) test remains a common method for detecting NDV antibodies and can effectively evaluate the level of immune antibodies and immune protection against the vaccine [ 16 , 17 , 18 , 19 , 20 ]. However, the HI test is complex and time-consuming to perform and requires specific specialist operators.…”
Section: Introductionmentioning
confidence: 99%